Making the Book of Kells - Thomas Keyes (EXARC Journal)
This article gives a brief history of the context of the Book of Kells before summarising recent research into its material makeup. It then goes on to introduce a possible site of production that has been excavated in the Scottish Highlands, before introducing a project to recreate a folio from the manuscript as an experimental archaeology project.